High expression of centromere protein N as novel biomarkers for gastric adenocarcinoma. Issue 4 (14th March 2023) - Wang, Xiaojie; Zhang, Keyuan; Fu, Cun; Wu, Fei; Zhang, Junjie; Han, Bin; Pan, Hai; Luan, Lan
Abstract: Background: The role and mechanism of centromeric protein N (CENP‐N), which has been associated with the development of various cancer types, are yet unclear in stomach adenocarcinoma (STAD). Methods: Data from the Cancer Genome Atlas and Genotype‐Tissue Expression were used to determine whether CENP‐N expression was altered in STAD tumors compared to normal tissues. Xiantao was used to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes(KEGG) enrichment analysis on CENP‐N. The relationship between CENP‐N expression and immune cell infiltration was assessed using TCGA database. The expression of CENP‐N in STAD and surrounding tissues was confirmed using immunohistochemical staining and the correlation between CENP‐N expression and clinicopathological characteristics was examined. The effects of CENP‐N knockdown by siRNA on proliferation were measured by CCK‐8 and EdU assays in AGS cells. Following siRNA transfection, flow cytometry was performed to evaluate cell cycle and apoptotic alterations in AGS cells. The effect of CENP‐N knockdown on the expression level of related proteins was detected by Westren blot. Results: CENP‐N was highly expressed in STAD tissues, which was confirmed by our immunohistochemistry results. The degree of invasion, TNM stage, and lymph node metastases were all strongly associated with CENP‐N expression. CENP‐N was essential for the cell cycle, DNA replication, chromosomal segregation, and nuclear division; there was a positive correlation between CENP‐N expression and infiltrating Th2 and NK CD56dim cells and a negative correlation between CENP‐N expression and mast, pDC, NK, and B cell infiltration. When CENP‐N expression in AGS cells was knocked down, cell proliferation dramatically reduced ( p < .05) and the percentage of cells in the S and G2‐M phases decreased significantly ( p < .05). Silencing CENP‐N significantly promoted the apoptosis of AGS cells ( p < .05). Mechanistic investigations showed that silencing CENP‐N expression may inhibit STAD proliferation through the Cyclin E1 and promote STAD apoptosis through the Bcl‐2/Bax. Conclusion: According to our data, CENP‐N acts as an oncogene in STAD and may be a viable therapeutic target.